RANCANG BANGUN APLIKASI SISTEM INFORMASI SHOW ME POSITION CHECKED BAGGAGE BERBASIS IoT - Muhammad Arsyil Axel; Ariyono Setiyawan; Laila Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
One of the service activities at the airport is the luggage service carried by passengers. There are two kinds of luggage carried by air transport passengers, namely checked baggage, which is the passenger's luggage that is handed over by the passenger at check-in to the aircraft operator to be transported by the airplane that the passenger is also boarding, and unchecked baggage which is luggage carried by passengers into the aircraft cabin, cabin baggage is under the supervision and responsibility of individual passengers. The development of the IoT-based Checked Baggage Position Update Information System Application is intended as a facility for Aircraft passengers to carry out tracking activities of their luggage. It is hoped that with the Information System Application that updates the position of this IoT-based checked baggage, it can increase the satisfaction and comfort of aircraft passengers with checked baggage handling services.The data used in this information system is an example of baggage data inputted by the admin. The next stage in the design, the researcher uses a planning tool in the form of a flowchart using a Flowchart and Unified Modeling Language System (UML) and is developed using a Software Content Management System (CMS). The method used in this research is Research and Development (R & D).